Core@double‐shell structured multifunctional phase change microcapsules based on modified graphene oxide Pickering emulsion. (10th October 2020) - Wei, Huan; Yang, Wenbin; He, Fangfang; Li, Yongsheng; Lou, Lan; Wang, Renchao; He, Ren; Fan, Jinghui; Zhang, Kai
Summary: New multifunctional phase change microcapsules with paraffin (Pn) as core and GO and lead tungstate (PbWO4 ) as double‐shell were designed by modified GO Pickering emulsion, and the effect of GO content on Pn@GO@PbWO4 microcapsules was studied. The morphology, chemical composition, and structure of Pn@GO@PbWO4 microcapsules were characterized, and their performance was studied in depth. The Pn@GO@PbWO4 microcapsules had a dense shell and a regular spherical structure. Compared with microcapsules without GO addition, the resultant Pn@GO@PbWO4 microcapsules could demonstrate high phase change reliability and thermal stability. Most of all, the anti‐seepage performance had been greatly improved by 67.27%. The results of contact angle (CA) measurement and gamma‐ray shielding test showed that the GO and PbWO4 double‐shell multifunctional microcapsules with superhydrophobic property and good gamma‐ray shielding property and high anti‐seepage performance had great attraction in expanding the application field of phase change materials. Abstract : A new multifunctional phase change microcapsules with paraffin as core and GO and PbWO4 as double‐shell were designed by GO Pickering emulsion, and the effect of GO content on Pn@GO@PbWO4 microcapsules was studied. The Pn@GO@PbWO4 microcapsules have enhanced thermal conductivity, leakage prevention, good energy storage ability, superhydrophobic behaviors, and gamma‐ray shielding performance. The microcapsules have potential applications in high‐tech systems such as buildings, intelligent fibers, or textiles, and wearable personal protection in nuclear power engineering.